Development of Video Media of School Health Services - ตันตรานนท์, กัลยาณี; สุริยะวงค์, วชิระ; ศรีเพชรวรรณดี, นพมาศ; เตือนราษฎร์, วิลาวัณย์; บุดดา, ดวงเดือน; นารินทร์, รังสิยา; ทรงคำ, วันเพ็ญ (Journal of The Royal Thai Army Nurses, 2019)
This study aimed to develop the video media of school health services. Samples were 4th year nursing students who registered in a community health nursing course (n = 50). A research instrument was questionnaires. Data was analyzed using descriptive statistic; percentage, average, and standard deviation. The results showed that most of the samples rated the usability and the users’ satisfaction scores in high level. The usability scores ranged from 4.54 to 4.80 (a total score was 5). Similarly, the average score of the users’ satisfaction ranged from 4.36 to 4.86 (a total score was 5). The results indicated that the video media was useful for nursing students in order to study the principle of school health services.